Using oral E. Coli milk vaccine to control colibacillosis - D A Schoneweis; V Gaeth (Kansas Agricultural Experiment Station Research Reports, 1978)
Colibacillosis is still a costly disease to swine producers in spite of new antibiotics and other products and procedures used to prevent or treat the disease. A recent aid in controlling the disease is the oral E. coli milk vaccine developed by Dr. Irvin Kohler. It consists of isolating a pathogenic E. coli from the herd and feeding the organism to pregnant sows to stimulate colostral antibodies. It is a giant step forward from the earlier recommendation of the late Dr. Howard Dunne who suggested taking the bedding and feces from the farrowing house and feeding it to pregnant sows to elevate the antibody content of the colostrum.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Oral E. coli milk vaccine; Colibacillosis